Mapping schools' NAPLAN results: a spatial inequality of school outcomes in Australia. (25th November 2018) - Smith, Crichton; Parr, Nick; Muhidin, Salut
Abstract: This article identifies spatial dimensions of educational outcomes using maps of the 2016 Grade 5 reading results for Australia's National Assessment Program–Literacy and Numeracy for all Australian schools. A geographical information system (GIS) was used to overlay schools' results onto suburbs' advantage or disadvantage to visualise spatial patterns. We then examined the extent to which school results "cluster" in socio‐economically advantaged and disadvantaged suburbs and considered the consistency of spatial patterns for results across major cities. That work illustrates both how GIS can foreground educational inequality and how "the spatial" is more than corollary for student socio‐economic status. Results show substantial differences between urban and remote areas and towns of different size. Maps of cities visualise spatial "clustering" patterns of school results, with most schools in advantaged suburbs having high results and almost no schools in disadvantaged suburbs having high results. Educational outcomes strongly align to local socio‐demographic characteristics, and parallel host communities' levels of advantage or disadvantage. Differences between public and private schools are less significant than within‐sector differences for schools in advantaged or disadvantaged locales. Patterns in all cities are consistent—schools in advantaged suburbs predominantly have high results, whereas non‐government schools generally perform better than government schools in disadvantaged suburbs. Most concerning is the persistent and increasing trajectory of results in advantaged, and more so in disadvantaged suburbs, of all cities since the first National Assessment Program–Literacy and Numeracy in 2008. Ameliorating spatial inequality between primary schools is one of the greatest challenges for Australians.